العلمانية السلبية "الـمحايدة" حتمية تاريخية لتطور العلاقة بين الدين والدولة ، أم مسايرة لـمفهوم الـمواطنة في الدولة القطرية الـمعاصرة - فرج, عبد الحميد (University of Eloued جامعة الوادي, 2022)
تتناول هذه الدراسة بالبحث مسألة مستجدة في الفكر السياسي الإسلامي ظهرت للواجهة بعد رسوخ مصطلح الدولة الوطنية القطرية المعاصرة وتزامن ذلك مع وصول بعض التيارات الإسلامية للسلطة ومحاولتها للموازنة بين ما تتبناه التيارات العلمانية العدائية للدين والمطالبة لإلغائه تماما من الحياة العامة بشتى أنوعها ، وبين الموروث الفكري لتلك التيارات والأحزاب السياسية ذات المرجعية الإسلامية قبل وصولها للسلطة ، حيث ينبت موقفا معتدلا بين الرأيين وهو اعتماد "العلمانية السلبية" أي العلمانية الغير معادية للدين ، وترك الأمر للمواطنين بتبني أي توجه ديني ، وحرية ممارسة شعائره الدينية التي يؤمن ويقتنع بها ، ولا تمنع تلك الممارسة أو تضيق عليها ، وهو ما تبناه حزب العدالة والتنمية في تركيا . Abstract: This study deals with the research of an emerging issue in Islamic political thought that appeared to the fore after the establishment of the term of the contemporary Qatari national state and this coincided with the arrival of some Islamic currents to power and their attempt to balance between what secular currents adopt hostile to religion and demand to completely eliminate it from public life of all kinds and the intellectual legacy of those currents And political parties with an Islamic reference before they came to power, where a moderate position arises between the two views, which is the adoption of "negative secularism", meaning secularism that is not hostile to religion, leaving the matter to citizens to adopt any religious orientation, and the freedom to practice his religious rituals that he believes and is convinced of, and this practice does not prevent or restrict On it, which was adopted by the Justice and Development Party in Turkey.
Negative " N eutral" S ecularism : A historical inevitability for the development of the relationship between R eligion and S tate , Or in keeping with the concept of C itizenship in the contemporary Qatari S tate
مقال
Keywords: العلمانية ; الدين ; المواطنة ; دولة وطنية; Secularism ; Religion ; Citizenship ; a nation state